2022
DOI: 10.1111/febs.16453
|View full text |Cite
|
Sign up to set email alerts
|

NMR and computational studies reveal novel aspects in molecular recognition of unsaturated fatty acids with non‐labelled serum albumin

Abstract: An approach based on the combined use of saturation transfer difference (STD), Tr-NOESY and Inter-ligand NOEs for PHArmacophore Mapping (INPHARMA) NMR techniques and docking calculations is reported, for the first time, for mapping interactions and specific binding sites of caproleic acid (10 : 1 cis-9), oleic acid (18 : 1 cis-9), linoleic acid (18 : 2 cis-9,12) and linolenic (18 : 3, cis-9,12,15) free fatty acids (FFAs) with non-labelled serum albumin (BSA/HSA). Significant negative inter-ligand NOEs between … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

7
25
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(32 citation statements)
references
References 55 publications
7
25
0
Order By: Relevance
“…Furthermore, although the serum albumin binding assay is the usual procedure for the development of new drugs, the binding modes of the polyunsaturated FFAs in Sudlow's sites I and II have not been elucidated. We report herein structural aspects of the binding modes of the polyunsaturated free fatty acids DHA and EPA to HSA with the combined use of saturation transfer difference (STD) [28][29][30], Tr-NOESY [31][32][33], and Interligand NOEs for Pharmacophore Mapping (INPHARMA) [26,27,[34][35][36] NMR techniques and molecular calculations [27,[34][35][36][37][38][39][40]. Particular emphasis was given to The various fatty acid and drug-binding sites have been investigated extensively over the past 40 years [12][13][14][15][18][19][20].…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…Furthermore, although the serum albumin binding assay is the usual procedure for the development of new drugs, the binding modes of the polyunsaturated FFAs in Sudlow's sites I and II have not been elucidated. We report herein structural aspects of the binding modes of the polyunsaturated free fatty acids DHA and EPA to HSA with the combined use of saturation transfer difference (STD) [28][29][30], Tr-NOESY [31][32][33], and Interligand NOEs for Pharmacophore Mapping (INPHARMA) [26,27,[34][35][36] NMR techniques and molecular calculations [27,[34][35][36][37][38][39][40]. Particular emphasis was given to The various fatty acid and drug-binding sites have been investigated extensively over the past 40 years [12][13][14][15][18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…Particular emphasis was given to The various fatty acid and drug-binding sites have been investigated extensively over the past 40 years [12][13][14][15][18][19][20]. X-ray crystallographic [16][17][18][21][22][23][24] and NMR [24][25][26][27] studies revealed the presence of seven to nine binding sites that may be occupied by both medium-and long-chain saturated fatty acids, with chain lengths from C10 to C18. FFA binding sites are asymmetrically distributed throughout the protein.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations